Development, Efficacy and Safety of Once-daily, Bedtime, Extended-release Amantadine (Gocovri®) to Treat Dyskinesia and OFF Time in Parkinson's Disease. Issue 1 (2021) - Isaacson, Stuart H; Lyons, Kelly E; Amjad, Fahd; Pahwa, Rajesh
No abstract available